PENGARUH DIMENSI KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PADA PT. UNITED TRACTORS TBK CABANG LAMPUNG - Ranti Noviyana; Stefanus Rumangkit (LP2M Universitas Bina Bangsa, 2021)
In a company, the most important thing is labor or human resources. Human resources are the most important assets driving company dynamics. Every company wants to excel in everything, especially in the field of work. This study aims to find the influence of Self-Awareness, Self-Regulation, Self-Motivation, Empathy and Social Skills on the performance of PT. United Tractors Tbk Lampung Branch. This type of research used in this research is a type of quantitative research using the associative method. The data source used is primary data. The data collection method used a questionnaire. The population in this study amounted to 33 employees of PT. United Tractors Tbk Lampung Branch. The sampling method in this research is nonprobability sampling and uses saturated sampling techniques. The results of the study show that SelfAwareness, Self-Regulation, Self-Motivation, Empathy and Social Skills have no effect on Employee Performance.